A framework of pavement management system based on IoT and big data. (January 2021) - Dong, Jichang; Meng, Weina; Liu, Ying; Ti, Jing
Abstract: With the expansion of urban road network, the importance of road maintenance is increasing, which guarantee the operation efficiency of transportation infrastructure. Compare to road construction, road maintenance is more sophisticated. Even though invested a lot of manpower and financial resources, management departments are troubled by insufficient and lagging road maintenance. The development and widely application of technologies including IoT, Big Data and Artificial Intelligence(AI) in various industries offer possible solutions to this issue. However, how to utilize these technologies is a challenge for related administration department because of their weak technical force. To address the problem, a pavement management system(PMC) is developed in this research. Combined with IoT and big data, the PMS provide an overall management structure of road maintenance. Composed of three subsections: Pavement detection and 3D modeling, Data analysis and Decision support, the PMS offer an automated and intelligent solution to related administrative departments and firms. Besides, two road maintenance related firms, one is a road maintenance company and the other is a technical firm that offer smart solutions to road maintenance, are selected as cases to illustrate how PMS are applied to support the daily operations and road maintenance.